Interactive Effect of Foreign Trade and Human Capital Development on Inclusive Growth in Nigeria (Integral Research, 2025)
This study was motivated by the persistent disparities in income distribution and limited access to the benefits of economic growth across different population groups in Nigeria. This study investigated the interactive effects of foreign trade and human capital development on inclusive growth. While foreign trade is often promoted as a catalyst for economic development, its ability to foster inclusive growth remains uncertain, especially in the absence of supportive human capital frameworks. This study investigated whether the synergistic combination of trade openness and human capital development could enhance growth inclusiveness. Data were collected from the World Development and the Central Bank of Nigeria Statistical Bulletin. The study adopted vector error correction modelling (VECM) to analyse both short-run and long-run dynamics. In the short run, the results showed that the interaction terms between trade openness and human capital proxies (life expectancy rate and secondary school enrolment rate) had mixed effects on inclusive growth. Meanwhile, the interactions between trade openness and life expectancy, and trade openness and secondary school enrolment were positive and significant in the long run. The study concluded that enhancing human capital, especially at the secondary education level, is crucial for maximising the inclusive potential of trade openness. Hence, the study recommended that the government should invest significantly in quality secondary education and strengthening the educational system; this will ensure that the workforce is better equipped to take advantage of the opportunities created by trade equitably distributed among the Nigerian population.
Keywords: Inclusive growth, trade openness, human capital development, education, life expectancy, Nigeria, VECM.